Evaluation of the technological, productive and economic results of the strategy for Tierra Blanca Extension Plan - Domínguez Torres, Victoria; Jaramillo Villanueva, José Luis; Macías Laylle, Alfonso; Estrella Chulim, Néstor; Martínez Domínguez, Marlene (Agricultura, Sociedad y Desarrollo, 2023)
The aim of this work was to evaluate the technological, economic and productive changes generated by the extension strategy “Plan Tierra Blanca” among the beneficiary agricultural producers, and generate recommendations for future interventions. The information was obtained by means of a probabilistic survey with a sample size of 66 producers, with precision of 10% and reliability of 95%. The data were collected in December 2018. Results showed that the average age of the head of family is 58 years, average schooling is 5 years; 80.3% of the interviewees are involved in agriculture as their main occupation. 66.7% are dedicated to planting maize as their main crop, the average size of the plots is 9.7 hectares, and the average area planted with maize is 2.2 hectares. The interviewees suffered losses to their crops or animals in 2018, mainly due to drought. In 2016, the second year operating PTB, there were higher yields, with an average of 4,369.8 kg/ha. In 2017, the mean seed, plant density, and yield (kg/ha) were statistically significant (p≤0.05), compared to the first year, whereas, in 2018, mean income from the sale of maize was also statistically significant.